The Sources of Social Economy. The Reasons for the Social Responsibility of Solidarity - George Neamţu (Annals of Philosophy, Social and Human Disciplines, 2012)
For the preoccupations of the theoretical and practice community development, Social Economy is the domain that holds the most of attention, especially after the formulation and the general objectives of Europe Agenda 2020. Furthermore, in most of the European Union countries there is a diverse and socio-professional impact network that is specific to the socio economy structures. Yet, even if there are some preoccupations in this direction, it has not reached a consensus in regard with the ideological sources of these particular types of organizations. Social enterprises / societies that are the most outspreaded social economy instruments, like corporate associations, are the best known structures of social economy, as well as other instruments specific to the domain, and have a high and outspread rate of appreciation within the society, but without clearly pointing out their theoretical foundation of their presence. We suggest the approach of this aspect from the perspective of a concept that is newly (re)formulated, that of Social Responsibility of Solidarity.1 This concept could explain the subtle mechanisms of the economical actors’ actions in the profit sector, actors who do not have yet as a main target the profit making that is the very base of Social Economy. Because, in the end it must be an answer to the question: why the companies sometimes behave like donors / philanthropists? The present study brings elements to complete the explicative theoretical pattern regarding economic organizations in respect with their atypical behavior from the area of social solidarity.